Influence of snow cover on the thermal regime of a polythermal glacier in Western Spitsbergen - A. V. Sosnovsky; Yu. Ya. Macheret; A. F. Glazovsky; I. I. Lavrentiev (Лëд и снег, 2015)
Influence of snow cover, climate and glacier parameters on the cold-ice layer thickness and thermal regime in the ablation area of a polythermal glacier in Western Svalbard was investigated. Numerical modeling has demonstrated that a thickness of a cold layer in a polythermal glacier depends on a relation between the ablation on the surface and the freezing rate at the layer base. If the ablation rate is lower than that of the freezing, the layer thickness grows until the ablation and freezing rates become equal. Estimations show that in a case of slightly negative air temperatures on the glacier its cold-ice layer thickness increases when the snow cover thickness grows.